Digital Infidelity, Women's Defamation, and Patriarchal Reproduction: Gender Reconstruction Through Critical Discourse Analysis and Mubādalah of Narrative on Instagram Accounts - Zarroq, Sulthan Aufa; Iffah, Iffah; Muktafi, Muktafi (ADDIN, 2026)
This study analyzes the construction of digital religious discourse regarding infidelity and the narrative of "women’s slander" in da'wah (preach) content on the Instagram of @raehanul_bahraen. Using the Critical Discourse Analysis (CDA) model of Teun A. van Dijk, this study examines how text structure, social cognition, and social context work simultaneously in shaping representations of gender relations and moral responsibility in the digital space. The research data were obtained through digital observation of da'wah uploads that explicitly refer to the hadith on women's slander, accompanied by analysis of captions, visuals, video narration, and audience comments as part of the discourse’s context. The analysis reveals a consistent pattern of discourse across the macro-, super-, and microstructures, in which men are positioned as subjects whose faith is tested. At the same time, women are portrayed as external sources of moral threats. This pattern is strengthened through religious lexical choices, rhetorical strategies in the form of appeals to authority, and individualistic framing of moral causality. The mubādalah (reciprocity) approach is used to re-read the hadith quoted in the discourse through the principle of reciprocity, so that moral responsibility is understood relationally and symmetrically between men and women. This research contributes theoretically by integrating CDA and the mubādalah approach in the analysis of digital da'wah, and empirically demonstrates how gender bias is reproduced and negotiated in religious communication on social media.